ABUSE OF ANABOLIC ANDROGENIC STEROIDS - Abbas Yavari (Journal of Stress Physiology & Biochemistry, 2009)
According to the International Olympic Committee, the abuse of anabolic androgenic steroids (AASS) is found in over 50% of positive doping tests. AASS abuse is not restricted to the organized sports andwidespread use. It remains as an unsolved public-health problem.Lower black market price, easier access to AASS, bodybuilding clubs and internet advertising are factors of this increasingly misuse. There is not real data about the prevalence of AASS abuse in various populations or countries, because most of athletes or students, due to their prohibition or ethical aspects do not admit to AASS abuse. Often they are aware of the risks of their choice and yet, are eager to put themselves at risk without deeper consideration. The abusers use them to improve their physical fitness and appearance.Present article has been collected to elucidate the risks and adverse effects of AASS and explanation of mechanisms of these events.